Students’ View on Criteria of Good Book for Online Business and Marketing Program - Naf’ihima, Fika Ar-Rizqi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL; Vol 2 No 1 (2020): Education and Linguistics Knowledge Journal (Edulink)DO - 10.32503/edulink.v2i1.995, 2020)
The book material for students can be said as a good book if they have fulfilled some criteria of good book. In line with this fact, this research has purpose to analyze the students‟ view on criteria of good book for online business and marketing. Besides, it also searches the students‟ needs of local wisdom material. The design is descriptive qualitative and the data is collected through observation, questionnaire, and interview. The observation was done through observe the recent english book from ministry of education and culture. The questionnaire was consisted of 22 questions and given to 36 students of online business and marketing program. The interview was given to English teacher and the students to get information about the recent english book, it also used to know the criteria of good book based on their perception. The preliminary research found that the recent english book material was not fulfilled some criteria of good book and local wisdom material was not found in this book. From this finding, need analysis is needed to know the criteria of good book based on students‟ view. The result finds that most of them need suitable english book material with the goal of their program, so it is in line and support the goal of vocational high school to prepare students in working world. Based on the finding from need analysis, English book material which is suitable with students need has to be developed. Moreover, this book should be based on local wisdom to promote local culture.